2007
DOI: 10.1055/s-2007-965080
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Anatomy of Shoot, Root, and Propagation Systems in Hoffmannseggia glauca

Abstract: Hoffmannseggia glauca is a perennial weed that has tubers and root-borne buds. Some authors only consider root tubers without mentioning root-borne buds, while others consider that more anatomic studies become necessary to determine the origin of these structures and to interpret their behaviour. The objectives are: to study the growth form of the plant in order to analyze the ontogeny of its propagation organs, and to study its shoot and root anatomical characters that affect water conductivity. Hoffmannseggi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Variability in root anatomy results mainly from the different origins of the cambium and its different products (Carlquist, 2001;Islam et al, 2007;Kraus and Basconsuelo, 2009;Kraus et al, 2003;Kraus et al, 2007;Metcalfe and Chalk, 1983;Rajput et al, 2006;Rajput, 2003). In the species belonging to the tribes Aeschynomeneae, Vicieae, and Trifolieae, the cambium results from a procambial remnant located between the xylem and the phloem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability in root anatomy results mainly from the different origins of the cambium and its different products (Carlquist, 2001;Islam et al, 2007;Kraus and Basconsuelo, 2009;Kraus et al, 2003;Kraus et al, 2007;Metcalfe and Chalk, 1983;Rajput et al, 2006;Rajput, 2003). In the species belonging to the tribes Aeschynomeneae, Vicieae, and Trifolieae, the cambium results from a procambial remnant located between the xylem and the phloem.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on legumes have demonstrated not only the diversity in the origin of the cambium (Carlquist, 2001;Metcalfe and Chalk, 1983) but also the occurrence of different cambial types, ranging from normal to more complex ones (Basconsuelo, 2004;Islam et al, 2007;Kraus and Basconsuelo, 2009;Kraus et al, 2003;Kraus et al, 2007;Kutschera and Lichtenegger, 1992;Lachaud et al, 1999;Milanez and Moraes-Dallaqua, 2003;Pate et al, 1989;Rajput et al, 2006;Rajput, 2003). In general, the majority of studies on legumes relate root anatomy to the environment rather than to systematics.…”
Section: Introductionmentioning
confidence: 99%
“…Such patterns include variation in vessel length, diameter and frequency; type of perforation plate; and axial and radial parenchyma with storage substances, among other features, which are mainly apparent in arboreal species (Kraus et al 2007;Carlquist 2009;Yang et al 2010), However, such tissues patterns in species of the herbaceous-subshrub stratum of most biomes is poorly known. Th e main challenge faced by anatomists is determining which anatomical changes are environmentally induced and which are a result of genetic alterations, which provides crucial anatomical responses and the interpretation of the adaptations of species to their environment (Metcalfe & Chalk 1979;Kraus et al 2010;Scremin-Dias et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research on variations in the secondary structure of roots and stems has been conducted mainly on woody lianas and trees rather than on herbaceous plants (Bamber and Ter Welle, 1994;Basconsuelo, 2001;Kraus et al 2007;Metcalfe and Chalk, 1983;Patel, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Anomalous secondary growth, which could be interpreted as habitat adaptation, has become a point of interest within the fields of systematics and phylogeny of dicotyledonous plants (Carlquist, 2003(Carlquist, , 2004(Carlquist, , 2007. Members of the Leguminosae family are well-known not only because of the diversity in the origin of the cambium but also because of the different cambial types they exhibit, ranging from normal cambia to more complex ones (Basconsuelo, 2001(Basconsuelo, , 2004Basson and Bierhorst, 1967;Handa, 1937;Kraus et al, 2003Kraus et al, , 2007Metcalfe and Chalk, 1983;Molina, 2007;Nair and Mohan Ram, 1990;Rajput, 2003;Rajput et al, 2006).…”
Section: Introductionmentioning
confidence: 99%